DICA endoscopic classification: 2-year analysis from an international, multicenter prospective study. (30th September 2020) - Nasi, G; Tursi, A; Di Mario, F; Elisei, W; Picchio, M; Bafutto, M; Dumitrascu, D; Regula, J; Mastromatteo, A M; Brandimarte, G
Abstract: Background: Diverticulosis of the colon is the most frequent anatomical alteration detected during colonoscopy. The endoscopic classification "DICA"(Diverticular Inflammation and Complication Assessment) has been recently developed in order to have an objective endoscopic description of the colon harbouring diverticula. Aim of this multicentre, international, prospective study was to assess the predictive value of this classification in term of acute diverticulitis and surgery occurrence on a 2-year observational follow-up period. Methods: 2215 prospective patients at the first diagnosis of diverticular disease were enrolled after exclusion of radiological signs of acute diverticulitis; inflammatory bowel diseases; ischemic colitis; prior colonic resection; patients with severe liver failure (Child-Pugh C) or severe kidney failure; pregnant women; patients who are currently using or who have received any laxative agents or mesalazine or probiotics or antibiotics < 2 weeks prior to the enrollment; inability to comply with study protocol; patients with or history of cancer, of any origin, within 5 years before enrollment; history of alcohol, drug, or chemical abuse. Results: 1377(62.15%) patients were classified as DICA 1, 599(27, 04%) as DICA 2 and 239(10.80%) as DICA 3. The risk of acute diverticulitis occurrence/recurrence, as well as the risk of surgery, were significantly linked to the severity of DICA score at entry. Overall, acute diverticulitis occurred in 123 (5, 5%) patients: it occurred in 32 (2, 3%) DICA 1, 53 (8, 9%) DICA 2 and 32 (16.4%) DICA 3 patients respectively (p < 0, 0001). Overall, surgery occurred in 35 (1, 6%) patients: it occurred in 2 (0.1%) DICA1, 15 (2, 5%) DICA 2 and 18 (7, 6%) DICA 3 patients respectively (p < 0, 0001). Conclusions: The 2-year results of this prospective study seems to confirm that DICA endoscopic classification has a significant prognostic role on the risk of acute diverticulitis occurrence/recurrence and surgery in these patients. Key messages: DICA is the first endoscopic classification of diverticular disease. The risk of occurrence/recurrence of acute diverticulitis and the risk of surgery are strictly linked to the severity of DICA score.